An informal school-based, peer-led intervention for prevention of tobacco consumption in adolescence: A cluster randomized trial in rural Gandhinagar - Anjali Sunil Kumar Mall; Aroor Bhagyalaxmi (Wolters Kluwer Medknow Publications, 2017)
Background: Tobacco use among adolescence is one of the important preventable causes of death as well as a leading public health problem all over the world. The present study was conducted with the objective of studying the effect of peer-led interventions on tobacco use among adolescents. Materials and Methods: Twenty schools were randomly selected and ten schools each were identified as cluster for intervention and control groups. A total of 402 students in intervention group and 422 in control group were studied. Results: About 48% and 41% of adolescents were consuming smokeless tobacco in any form in the intervention and control groups, respectively. Prevalence of consumption of smokeless tobacco was significantly high among boys as compared to girls. Pan masala was the most common form of consumption. After conducting A Stop Smoking in School Trial-like peer-led intervention, a significant reduction in tobacco consumption of any form was observed in the intervention group (48%-36%) during the follow-up (Z = 3.2, P < 0.01). A significant reduction in exposure to passive smoking in the intervention group (32%-29%) was also observed. All the students smoking initially had stopped smoking at the end of the follow-up in both the groups. Conclusion: It was found that peer-led intervention was effective in reducing the consumption of smokeless tobacco in any form. The rate of reduction was more in the first follow-up as compared to the end of the intervention. Sustained intervention in the form of retraining is needed for the long-term effect.